The Influence of Operating Cash Flow, Current Ratio, and Solvability Ratio on Profit Margin in Service Companies (Open Society Conference, 2024)
This research aims to determine the influence of operating cash flow, current ratio and solvency ratio on profit margin in service companies in the financial institution sub-sector listed on the Indonesia Stock Exchange in 2019-2022. This research uses a type of quantitative research which is measured using a regression-based method, namely the t test and f test using the Eviews version 12 program. The data used in this research is secondary data. The data obtained is pool data. Data collection was obtained from 9 companies consisting of 36 reports finance. The sampling method uses purposive sampling technique. Data source obtained from www.idx.co.id. The research results prove that (1) operating cash flow has an effect on profit margin, (2) the current ratio has no effect on profit margin, (3) the solvability ratio has no effect on profit margin, (4) the influence of the current ratio and the solvency ratio simultaneously has an effect on profit margin.